2016
DOI: 10.1111/cch.12425
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of developmental surveillance completion at six months of age in south western Sydney

Abstract: BackgroundWhile developmental surveillance programs promote early identification of child developmental problems, evidence has indicated suboptimal uptake. This study aimed to identify predictors of developmental surveillance completion at 6 months postpartum.MethodsQuestionnaires were administered to the parents of 510 infants who were born in south western Sydney, Australia over a 22‐month period. Attendance for developmental screening and completion of the Parents' Evaluation of Developmental Status (PEDS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Because of this relative paucity of information from Australia, a longitudinal birth cohort ‘Watch Me Grow’ study has recently been conducted in the South Western Sydney (SWS) region of New South Wales. This study confirmed previous international research on factors affecting WCC and developmental screening activities [ 25 , 26 ]. However, there is an absence of research that directly observes “real life” WCC visits between GP’s and parents with young children in the context of the Australian public health system.…”
Section: Introductionsupporting
confidence: 91%
“…Because of this relative paucity of information from Australia, a longitudinal birth cohort ‘Watch Me Grow’ study has recently been conducted in the South Western Sydney (SWS) region of New South Wales. This study confirmed previous international research on factors affecting WCC and developmental screening activities [ 25 , 26 ]. However, there is an absence of research that directly observes “real life” WCC visits between GP’s and parents with young children in the context of the Australian public health system.…”
Section: Introductionsupporting
confidence: 91%
“…The WMG longitudinal birth cohort study was established in the South Western (SW) Sydney region with the broad aim of generating robust evidence to inform policy makers and service providers on maximizing the uptake of the developmental surveillance program [ 41 ]. The description of the study cohort and quantitative evidence assessing the risk factors and prevalence of parental developmental concerns for their children has been reported elsewhere [ 42 44 ]. We have also recently reported the findings from the qualitative component of the study on the parent’s experiences for accessing services for their children’s health and development [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Language barriers contribute to a lack of knowledge of the disease, treatment, and prevention, disempowerment, and isolation of the patient and family members (Heywood & López‐Vélez, 2019). Culturally and linguistically diverse parents are 1.3 times more likely to leave the hospital with their child against medical advice, 1.6 times as likely to leave emergency departments left against the advice or did not wait to be seen, and 1.5 times more likely to not show for an outpatient appointment (Guo et al, 2019), or be unaware of the services available to them (Garg et al, 2017; Overs et al, 2017). Our findings also highlighted that Australia's First People who, although born in Australia, may not report English as a preferred language and therefore experience healthcare barriers (Goldfeld et al, 2011; Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%